German veterinarians asked: a cross-sectional study on microbiological examination and antimicrobial use in canine reproductive medicine - Rojahn, Alicia; Leps, Anna Sophia; Goericke-Pesch, Sandra (Frontiers in Veterinary Science, 2025)
Despite the growing global threat of antimicrobial resistance, many dog breeders still request antimicrobial treatment prior to mating, often based on vaginal bacterial culture examinations. However, several previous studies failed to identify differences in the vaginal microbiota between healthy dogs and those with reproductive tract disorders; thus, treating healthy bitches with antimicrobials regardless of the bacterial findings is contraindicated. To investigate current practices of German small animal veterinarians regarding microbiological sampling and antimicrobial treatment in canine reproductive medicine, we conducted an online survey using LimeSurvey®. The questionnaire included questions (single/multiple choice) about procedures of microbiological swab sampling and handling in general and in canine reproductive medicine specifically, as well as on antimicrobial use in the respective field. The objective was to identify educational and research needs regarding vaginal bacterial culture interpretation and antimicrobial treatment in canine breeding. We found that treating clinically healthy breeding bitches remains common practice among both breeders and veterinarians. Our findings highlight the importance of continuous education and improved communication to reduce inappropriate antimicrobial use in canine reproduction. Furthermore, research on the reproductive microbiome in relation to fertility is essential for evidence-based treatment decisions.